A preparation method of EVA material and EVA material

Through mechanical blending and transesterification reaction, EVA materials with dynamic crosslinking bonds are prepared, which solves the problem of difficulty in recycling and utilization of traditional EVA materials, and achieves high efficiency recovery and good performance after multiple cycles.

CN115073773BActive Publication Date: 2025-05-06LIMING VOCATIONAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210837196.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2025-05-06
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

Irreversible chemical crosslinking of traditional EVA materials makes it difficult to recycle and reuse. Existing recycling methods such as incineration and crushing are low, and the compatibility of the crushed EVA rubber particles after crosslinking is poor with the new material.

Method used

The mechanical blending method is used to prepare EVA materials with dynamic crosslinking bonding by using transesterification reaction under the action of a catalyst. The method includes predispersing the filler particles in a solvent, adding an ester silane coupling agent for modification, forming a dynamic crosslinking agent, and blending with the EVA raw material in a torque rheometer, followed by vulcanization and molding.

Benefits of technology

The crosslinked EVA material can be recycled and processed by conventional plastic hot processing methods, and after multiple cycles of processing, it still maintains good mechanical properties and physical mechanical properties, and has a relatively high utilization rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115073773B_ABST
    Figure CN115073773B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an EVA material, comprising the steps of preparation, cross-linking and molding. The present invention also provides an EVA material obtained by the above-mentioned preparation method. The present invention adopts a mechanical blending method and utilizes an ester exchange reaction under the action of a catalyst to obtain an EVA material with dynamic cross-linking bonds, and the dynamic cross-linking bonds enable the cross-linked EVA to be recycled by a conventional plastic heat processing method, and still maintain good mechanical properties after multiple cycles of processing, and maintain a relatively high utilization rate of good physical and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an EVA material, in particular to a preparation method of the EVA material and the EVA material. Background Art

[0002] The continuous development of the global plastics industry has brought great convenience to life, but it has also generated a large amount of plastic waste worldwide. Therefore, developing sustainable plastics with longer service life, upgrading and recycling or reusing post-consumer polymers is one of the effective ways to reduce plastic waste.

[0003] After cross-linking and foaming, ethylene-vinyl acetate copolymer (EVA) plastic products have excellent properties such as softness, good elasticity, and chemical corrosion resistance. They are widely used in the soles and interior materials of mid-to-high-end tourist shoes, mountaineering shoes, and sports shoes. The traditional EVA cross-linking method mainly uses irreversible chemical cross-linking, which poses a great challenge to the recycling or reuse of EVA.

[0004] At present, waste EVA is mainly disposed of by incineration to obtain heat and reprocessing. Incineration to obtain heat is relatively simple, but incineration will produce toxic chemicals and the utilization rate is low; reprocessing mainly involves chopping and grinding the cross-linked EVA into fine powder, and using it as a filler to replace part of the new EVA material, which is the main method for recycling cross-linked EVA. However, the compatibility of the crushed EVA particles after cross-linking with the new EVA material is low, so it can only be added or replaced in small amounts, and the utilization rate is low.

[0005] In view of this, the applicant conducted an in-depth study on the above-mentioned issues, which led to the present case. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing an EVA material with relatively high utilization rate and an EVA material.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing an EVA material comprises the following steps:

[0009] S1, preparation, placing filler particles in a container, and pre-dispersing the filler particles in a toluene solvent or an ethanol solvent to obtain a suspension, then adding an ester silane coupling agent to the suspension, obtaining a mixture after a modification reaction, subjecting the mixture to a centrifugal washing treatment to obtain a filter residue, and then drying the filter residue to obtain a dynamic crosslinking agent;

[0010] S2, cross-linking, adding EVA raw materials into a torque rheometer for pre-dispersion, and then adding an ester exchange catalyst and the dynamic cross-linking agent into the torque rheometer for blending to obtain a blend;

[0011] S3, molding, sequentially performing vulcanization treatment and compression molding on the blend to obtain an EVA material.

[0012] As an improvement of the present invention, in step S1, the ester silane coupling agent is added to the container in 3-5 times, and the solution in the container is stirred while adding the ester silane coupling agent, the stirring speed of the stirring treatment is 500-1500r / min, and then condensed and refluxed at 70-110°C for 2h.

[0013] As an improvement of the present invention, the filler particles are silicon dioxide and / or calcium carbonate, the particle size of the filler particles is 20 to 2000 nm, the mass fraction of the filler particles is 1%-10%, the ester silane coupling agent is one or two of 2-carbonylmethoxyethyldimethoxymethylsilane, acetoxypropyltrimethoxysilane, 3-(carbonylmethoxy)propyldimethylmethoxysilane and 3-(carbonylethoxy)propyldimethylethoxysilane, the EVA raw material is a thermoplastic unvulcanized cross-linked EVA with an ethyl acetate content of 10-30%, and the ester exchange catalyst is tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate or acetyl molybdenum.

[0014] As an improvement of the present invention, in step S1, the filler particles are pre-dispersed by ultrasound at 20-40°C for 20-40 minutes.

[0015] As an improvement of the present invention, in step S1, during the centrifugal washing treatment, the mixture is centrifuged at a speed of 8000-12000 r / min for 3-5 times, and each centrifugal treatment lasts for 3-7 minutes.

[0016] As an improvement of the present invention, in step S1, during the drying process, the filter residue is vacuum dried at 80-120° C. for 8-20 h.

[0017] As an improvement of the present invention, in step S2, the reaction temperature of the torque rheometer is controlled to be 100-180° C. and the rotation speed is controlled to be 50-200 rpm.

[0018] As an improvement of the present invention, in step S2, the pre-dispersion time is 5-10 minutes, the ester exchange catalyst is added to the torque rheometer 3-5 times, and then mixed for 10-30 minutes, and then the dynamic crosslinking agent is added to the torque rheometer 3-5 times, and then blended for 10-30 minutes.

[0019] As an improvement of the present invention, in step S3, during compression molding, the compression pressure is 5-20 MPa, the compression temperature is 120-180° C., and the compression time is 0.5-2 h.

[0020] An EVA material comprises 10-30 parts by mass of filler particles, 1-10 parts by mass of an ester silane coupling agent, 70-100 parts by mass of EVA, 0.1-2.5 parts by mass of an ester exchange catalyst and 1-10 parts by mass of a dynamic crosslinking agent, and is prepared by adopting the above-mentioned preparation method of the EVA material.

[0021] By adopting the above technical solution, the present invention has the following beneficial effects:

[0022] The present invention adopts a mechanical blending method and utilizes an ester exchange reaction under the action of a catalyst to obtain an EVA material with dynamic cross-linking bonds. The dynamic cross-linking bonds enable the cross-linked EVA to be recycled by a conventional plastic heat processing method, and to maintain good mechanical properties after multiple cycles of processing, and to maintain good physical and mechanical properties, with a relatively high utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of the dynamic cross-linking agent in the embodiment;

[0024] Figure 2 This is a scanning electron microscope image of the EVA-1 foam material in Example 3;

[0025] Figure 3 This is a scanning electron microscope image of the EVA-2 foam material in Example 3;

[0026] Figure 4 This is a scanning electron microscope image of the EVA-3 foam material in Example 3.

[0027] The symbols in the figure correspond to the following:

[0028] 1-filler particles; 2-ester silane coupling agent. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments. The raw materials and test instruments used in the following embodiments and comparative examples can be purchased directly from the market. The test steps or test steps for which specific conditions are not specified are all carried out under conventional conditions or under the conditions recommended by the test instrument manufacturer and will not be described in detail here.

[0030] The present invention provides a method for preparing an EVA material, wherein a multi-crosslinked EVA material is prepared by a mechanical blending method using an ester exchange reaction between a carboxylic acid ester contained in the EVA and a crosslinking agent containing a polyalkyl ester, and the dynamics of the crosslinked network is controlled by changing the use and type of the crosslinking agent, thereby regulating the dynamic crosslinking structure and physical and mechanical properties of the EVA material. The method comprises the following steps:

[0031] S1. Preparation: placing filler particles in a container, wherein the filler particles may be silicon dioxide and / or calcium carbonate, the particle size of the filler particles is 20 to 2000 nm, and the mass fraction of the filler particles is 1% to 10%.

[0032] Then, the filler particles are pre-dispersed in a toluene solvent or an ethanol solvent to obtain a uniform suspension. Specifically, the filler particles are pre-dispersed for 20-40 minutes using ultrasound at 20-40° C. Then, an ester silane coupling agent is added to the suspension, and a mixture is obtained after a modification reaction, wherein the ester silane coupling agent can be one or two of 2-carbonylmethoxyethyldimethoxymethylsilane, acetoxypropyltrimethoxysilane, 3-(carbonylmethoxy)propyldimethylmethoxysilane and 3-(carbonylethoxy)propyldimethylethoxysilane. Preferably, the ester silane coupling agent is added to the container in 3-5 times, and the solution (and suspension) in the container is stirred while the ester silane coupling agent is added. The stirring speed of the stirring treatment is 500-1500r / min, and then condensed and refluxed at 70-110° C. for 2h.

[0033] The mixture is subjected to centrifugal washing to obtain a filter residue. During the centrifugal washing, the mixture is centrifuged at a speed of 8000-12000 r / min for 3-5 times, and each centrifugal treatment lasts for 3-7 minutes. The filter residue is then dried to obtain a dynamic crosslinking agent. During the drying, the filter residue is vacuum dried at 80-120°C for 8-20 hours. Figure 1 As shown, the dynamic crosslinking agent obtained in the present invention has a hard segment structure mainly formed by filler particles 1, and the ester silane coupling agent 2 is connected by the hard segment structure, which has good stability.

[0034] S2, cross-linking, put EVA raw material into the torque rheometer and pre-disperse, control the reaction temperature of the torque rheometer to be 100-180°C, the rotation speed to be 50-200rpm, and the pre-dispersion time to be 5-10min. It should be noted that the above EVA raw material is a thermoplastic unvulcanized cross-linked EVA with an ethyl acetate content of 10-30%.

[0035] Then, the ester exchange catalyst and the dynamic crosslinking agent are added to the torque rheometer for blending treatment to obtain a blend, wherein the ester exchange catalyst is tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate or acetyl molybdenum. The ester exchange catalyst is added to the torque rheometer in 3-5 times, and then mixed for 10-30 minutes, and then the dynamic crosslinking agent is added to the torque rheometer in 3-5 times, and then blended for 10-30 minutes.

[0036] S3, molding, sequentially subjecting the blend to vulcanization treatment and compression molding to obtain EVA material, wherein the vulcanization treatment is performed using a flat vulcanizer, and during compression molding, the molding pressure is 5-20 MPa, the molding temperature is 120-180° C., and the molding time is 0.5-2 h.

[0037] The present invention also provides an EVA material, comprising 10-30 parts by mass of filler particles, 1-10 parts by mass of an ester silane coupling agent, 70-100 parts by mass of EVA, 0.1-2.5 parts by mass of an ester exchange catalyst and 1-10 parts by mass of a dynamic crosslinking agent, and is prepared by the above-mentioned preparation method of the EVA material.

[0038] The present invention avoids the traditional irreversible chemical cross-linking method and uses the ester exchange reaction between the carboxylic acid ester contained in EVA and the specific cross-linking agent containing polyalkyl esters to prepare the poly-cross-linked EVA material. EVA contains a large number of C=O bonds. The presence of unsaturated bonds makes EVA sensitive to ultraviolet radiation, easy to be oxidized, and has poor weather resistance. It is easy to age and fail after long-term exposure. Dynamic cross-linked EVA is formed through ester exchange, which reduces the content of unsaturated double bonds in the polymer, effectively improves its anti-ultraviolet performance and high temperature stability, and prolongs the service life. Compared with traditional thermoplastics, due to the formation of a cross-linked network, the network helps to stabilize the molecular structure during the reprocessing process and prevent the breakage of the polymer chain. The invention adopts a pre-hydrolysis reaction of an ester-containing silane coupling agent and filler particles to obtain an ester-based dynamic crosslinking agent with a hard segment (filler particle) structure. Under the action of an ester exchange catalyst, the ester-based dynamic crosslinking agent and the carboxylic acid ester of EVA undergo an ester exchange reaction to prepare a multi-crosslinked EVA material, which shows good reprocessability and maintains good physical and mechanical properties. Reinforcement particles are embedded in the EVA molecular chain, avoiding the agglomeration problem caused by simple mechanical blending, and effectively improving the mechanical properties of the EVA material that can be recycled.

[0039] The preparation method of the EVA material and the EVA material of the present invention are further described below through several embodiments and comparative examples.

[0040] Example 1

[0041] According to the preparation method of the above EVA material, 20g of silica was pre-dispersed in 500mL of toluene solution, ultrasonically dispersed at 25°C for 30min, 3g of 2-carbonylmethoxyethyldimethoxymethylsilane was added, and stirred with an external electric stirrer, the stirrer speed was controlled to 800r / min, the reaction temperature was 80°C, and the condensation reflux reaction was carried out for 2h. The mixture was centrifuged and washed 5 times at 8000r / min, each time for 5min, to obtain a filter residue, and the filter residue was vacuum dried at 100°C for 15h to obtain an ester silane coupling agent grafted silica dynamic crosslinking agent.

[0042] In the torque rheometer, 100g of EVA (product name is DuPont 770) was put into the torque rheometer, the temperature of the torque rheometer was controlled to be 130°C, the rotation speed was 100rpm, and pre-mixing was performed for 5min; 6g of tetrabutyl titanate catalyst was added and blended for 5min; 8g of dynamic cross-linking agent was added and blended for 30min to obtain a blend. After standing for a period of time, the blend was placed in a flat vulcanizer for vulcanization treatment and compression molding. The compression molding pressure was 10Mpa, the compression temperature was 120°C, and the compression time was 2.5h to obtain EVA-0 material.

[0043] Finally, the dynamic cross-linking structure is not destroyed and recycled for reuse: the EVA-0 material is cut into 0.5-2 cm blocks, and the compression molding steps are repeated to obtain EVA-1 material (i.e., the EVA material that has been recycled for the first time); then the shearing and compression molding steps are repeated to obtain EVA-n, where n represents the number of times it has been recycled; for example, EVA-0 means that it has not been recycled, and EVA-1 means that EVA-0 has been recycled once to obtain EVA-1.

[0044] Example 2

[0045] According to the preparation method of the EVA material, 20g of calcium carbonate was pre-dispersed in 500mL of ethanol solution, ultrasonically dispersed at 25°C for 30min, 10g of acetoxypropyltrimethoxysilane was added, and stirred with an external electric stirrer, the stirrer speed was controlled to 800r / min, the reaction temperature was 80°C, and the condensation reflux reaction was carried out for 2h. The mixture was centrifuged and washed 5 times at 8000r / min, each time for 5min, to obtain a filter residue, and the filter residue was vacuum dried at 100°C for 15h to obtain an ester silane coupling agent grafted calcium carbonate dynamic crosslinking agent.

[0046] In the torque rheometer, 100g of EVA (product name is DuPont 53071) was added, the temperature of the torque rheometer was controlled to be 130°C, the rotation speed was 100rpm, and pre-mixing was performed for 5min; 1.5g of acetyl molybdenum (analytical grade) was added and blended for 5min; 8g of dynamic cross-linking agent and 5g of calcium carbonate were added, and blended for 30min to obtain a blend; the blend was placed in a flat vulcanizer for vulcanization treatment and compression molding, the molding pressure of the compression molding was 10MPa, the molding temperature was 150°C, and the molding time was 2h to obtain EVA-0 material.

[0047] Finally, the dynamic cross-linking structure is not destroyed and recycled: the EVA-0 material is sheared into 0.5-2 cm blocks, and the compression molding steps are repeated to obtain the EVA-1 material; then the shearing and compression molding steps are repeated to obtain EVA-n.

[0048] Example 3

[0049] According to the preparation method of the above EVA material, 20g of silica was pre-dispersed in 500mL of toluene solution, ultrasonically dispersed at 25°C for 30min, 7g of 3-(carbonylmethoxy)propyldimethylmethoxysilane was added, and stirred with an external electric stirrer, the stirrer speed was controlled to 800r / min, the reaction temperature was 80°C, and the condensation reflux reaction was carried out for 2h. The mixture was centrifuged and washed 5 times at 8000r / min, each time for 5min, to obtain a filter residue, and the filter residue was vacuum dried at 100°C for 15h to obtain an ester silane coupling agent grafted silica dynamic crosslinking agent.

[0050] In the torque rheometer, 100g of EVA (product name is DuPont 53071) was added, the temperature of the torque rheometer was controlled to be 130°C, the rotation speed was 100rpm, and pre-mixing was performed for 5min; 1.5g of tetrabutyl titanate was added and blended for 5min; 9g of dynamic cross-linking agent was added and blended for 30min to obtain a blend; the blend was placed in a flat vulcanizer for vulcanization treatment and compression molding, the molding pressure of the compression molding was 10MPa, the molding temperature was 150°C, and the molding time was 2h to obtain EVA-0 material.

[0051] Finally, the dynamic cross-linking structure was destroyed for recycling: the EVA-0 material was put back into the torque rheometer, the reaction temperature was controlled at 120°C and the rotation speed was 70 rpm. After completion, it was compression molded again to obtain EVA-1. The steps of re-putting into the torque rheometer and compression molding were repeated to obtain EVA-n.

[0052] Example 4

[0053] The preparation method of Example 3 was repeated, but 8 g of dynamic cross-linking agent was added (i.e., the dynamic cross-linking agent content in Example 3 was changed from 9 g to 8 g), and then 3 g of ADC foaming agent (product name: Junpeng HG2097-91) was added, and then blended for 30 minutes. The contents of the remaining components remained unchanged to obtain an EVA-0 foaming material.

[0054] The dynamic cross-linking structure is destroyed for recycling and reuse: the EVA-0 material is put back into the torque rheometer, the reaction temperature is controlled to 120°C, the rotation speed is 70rpm, and 3g of ADC foaming agent is added. After completion, it is compression molded again to obtain EVA-1, and the steps of re-putting into the torque rheometer and compression molding are repeated to obtain EVA-n.

[0055] Comparative Example 1

[0056] Referring to step S2 and step S3 in the preparation method of the above-mentioned EVA material, 100g of EVA (DuPont 53071) was put into the torque rheometer, the temperature of the torque rheometer was controlled to be 130°C, the speed was 100rpm, and the premixing was performed for 5min; 1.5g of tetrabutyl titanate was added and blended for 5min; 9g of unmodified silica was added and blended for 30min to obtain a blend; the blend was placed in a flat vulcanizer for vulcanization treatment and compression molding, the molding pressure of the compression molding was 10MPa, the molding temperature was 150°C, and the molding time was 2h to obtain EVA-0 material.

[0057] The dynamic cross-linking structure is destroyed for recycling: the EVA-0 material is put back into the torque rheometer, the reaction temperature is controlled at 120°C and the rotation speed is 70 rpm. After completion, it is compression molded again to obtain EVA-1. The steps of re-putting into the torque rheometer and compression molding are repeated to obtain EVA-n.

[0058] Comparative Example 2

[0059] Referring to the preparation method of the above-mentioned EVA material, 20 parts by mass of silica were pre-dispersed in 500 mL of toluene solution, ultrasonically dispersed at 25°C for 30 minutes, and conventional silane coupling agent KH560 was added. The mixture was stirred with an external electric stirrer, the stirrer speed was controlled to 800r / min, the reaction temperature was 80°C, and the reaction was condensed and refluxed for 2 hours. The mixture was centrifuged and washed 5 times at 8000r / min, each time for 4 minutes, to obtain a filter residue, which was vacuum dried at 100°C for 12 hours to obtain coupling agent KH560 grafted silica.

[0060] In the torque rheometer, 100g of EVA (product name is DuPont 53071) was added, the temperature of the torque rheometer was controlled to be 130°C, the rotation speed was 100rpm, and pre-mixing was performed for 5min; 1.5g of tetrabutyl titanate was added and blended for 5min; 9g of coupling agent KH560 silica was added and blended for 30min to obtain a blend; the blend was placed in a flat vulcanizer for vulcanization treatment and compression molding, the molding pressure of the compression molding was 10MPa, the molding temperature was 150°C, and the molding time was 2h to obtain EVA-0 material.

[0061] The dynamic cross-linking structure is destroyed for recycling: the EVA-0 material is put back into the torque rheometer, the reaction temperature is controlled at 120°C and the rotation speed is 70 rpm. After completion, it is compression molded again to obtain EVA-1. The steps of re-putting into the torque rheometer and compression molding are repeated to obtain EVA-n.

[0062] Comparative Example 3

[0063] Referring to step S2 and step S3 in the preparation method of the above-mentioned EVA material, 100g of EVA (product name is DuPont 53071) is put into a torque rheometer, the torque rheometer temperature is controlled to be 130°C, the speed is 100rpm, and the premixing is 5min; 1.5g of tetrabutyl titanate is added and blended for 5min; 20g of silicon dioxide and 7g of diisopropylbenzene peroxide (DCP cross-linking agent) are added, and blended for 30min to obtain a blend; the blend is placed in a flat vulcanizer for vulcanization treatment and compression molding, the compression molding molding pressure is 10MPa, the compression temperature is 150°C, and the compression time is 2h to obtain EVA-0 material.

[0064] The dynamic cross-linking structure is destroyed for recycling: the EVA-0 material is put back into the torque rheometer, the reaction temperature is controlled at 120°C and the rotation speed is 70 rpm. After completion, it is compression molded again to obtain EVA-1. The steps of re-putting into the torque rheometer and compression molding are repeated to obtain EVA-n.

[0065] The physical and mechanical properties of the EVA materials obtained in the above embodiments and comparative examples were tested, and the results are shown in the following table.

[0066]

[0067]

[0068] As can be seen from the above table, the regenerated EVA obtained in Example 3 has the best effect, and the performance of the EVA regenerated foaming material obtained in Example 4 is better, satisfying the molar ratio of ethyl acetate content of EVA to cross-linking agent triisobutyl borate of 3:1; Comparative Example 1, the amount of ester silane coupling agent is 3g, and the tensile strength of the EVA material obtained due to insufficient cross-linking is low; Comparative Example 2, the amount of dynamic cross-linking agent is 10g, and multiple cross-linking; Comparative Example 1, directly adding silica and 3-(carbonylmethoxy)propyldimethylmethoxysilane in the torque rheometer, silica is not pre-grafted with ester silane coupling agent to obtain dynamic cross-linking agent, and no effective cross-linking system is formed; Comparative Example 2, adopting KH560 silane coupling agent, improves the compatibility of silica and EVA, and improves mechanical properties, but no effective cross-linking system is formed; Comparative Example 3, directly adopting the traditional DCP cross-linking agent method, the obtained EVA material has better performance, but cannot be recycled.

[0069] The EVA foam material obtained in Example 3 was observed and photographed by a scanning electron microscope. The obtained photographs are as follows: Figure 2-Figure 4 As shown in the figure, it can be seen that the pore diameter is 50-150 μm, the foam has a closed-cell structure and has good shrinkage resistance.

[0070] The present invention has been described in detail above with reference to specific embodiments. However, the embodiments of the present invention are not limited to the above embodiments. Those skilled in the art can make various modifications to the present invention based on the prior art, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing an EVA material, characterized in that: The following steps are involved: S1. Preparation, placing filler particles in a container, and pre-dispersing the filler particles in a toluene solvent or an ethanol solvent to obtain a suspension, then adding an ester silane coupling agent to the suspension, obtaining a mixture after a modification reaction, subjecting the mixture to a centrifugal washing treatment to obtain a filter residue, and then drying the filter residue to obtain a dynamic crosslinking agent; the filler particles are silicon dioxide and / or calcium carbonate, the particle size of the filler particles is 20 to 2000 nm, the mass fraction of the filler particles is 1%-10%, and the ester silane coupling agent is one or two of 2-carbonylmethoxyethyldimethoxymethylsilane, acetoxypropyltrimethoxysilane, 3-(carbonylmethoxy)propyldimethylmethoxysilane and 3-(carbonylethoxy)propyldimethylethoxysilane; the mass fraction of the filler particles is 10-30 parts, and the mass fraction of the ester silane coupling agent is 1-10 parts; S2, cross-linking, adding EVA raw material into the torque rheometer for pre-dispersion, and then adding the ester exchange catalyst and the dynamic cross-linking agent into the torque rheometer for blending treatment to obtain a blend; the EVA raw material is a thermoplastic unvulcanized cross-linked EVA with an ethyl acetate content of 10-30%, and the ester exchange catalyst is tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate or acetyl molybdenum; the mass parts of the EVA are 70-100 parts, the mass parts of the ester exchange catalyst are 0.1-2.5 parts, and the mass parts of the dynamic cross-linking agent are 1-10 parts; S3, molding, sequentially performing vulcanization treatment and compression molding on the blend to obtain an EVA material.

2. The method for preparing the EVA material according to claim 1, wherein In step S1, the ester silane coupling agent is added to the container in 3-5 times, and the solution in the container is stirred while adding the ester silane coupling agent, the stirring speed of the stirring treatment is 500-1500 r / min, and then condensed and refluxed at 70-110° C. for 2 hours.

3. The preparation method of the EVA material as claimed in claim 1, characterized in that, In step S1, the filler particles are pre-dispersed by ultrasound at 20-40°C for 20-40 minutes.

4. The method for preparing the EVA material according to claim 1, wherein: In step S1, during the centrifugal washing treatment, the mixture is centrifuged at a speed of 8000-12000 r / min for 3-5 times, and each centrifugal treatment lasts for 3-7 min.

5. The method for preparing the EVA material according to claim 1, wherein: In step S1, during the drying process, the filter residue is vacuum dried at 80-120° C. for 8-20 h.

6. The method for preparing the EVA material according to claim 1, characterized in that: In step S2, the reaction temperature of the torque rheometer is controlled to be 100-180° C. and the rotation speed is controlled to be 50-200 rpm.

7. The method for preparing the EVA material according to claim 1, characterized in that: In step S2, the pre-dispersion time is 5-10 minutes, the transesterification catalyst is added to the torque rheometer in 3-5 times, and then mixed for 10-30 minutes, and then the dynamic crosslinking agent is added to the torque rheometer in 3-5 times, and then blended for 10-30 minutes.

8. The method for preparing the EVA material according to claim 1, wherein: In step S3, during compression molding, the compression pressure is 5-20 MPa, the compression temperature is 120-180°C, and the compression time is 0.5-2h.

9. An EVA material, characterized in that: The EVA material is prepared by the preparation method of the EVA material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Thermo-mechanically-recoverable crosslinked cable material and preparation method thereof

    CN109694538A

  • Recyclable EVA virimer foam material, and preparation method and recycling method thereof

    CN111218054A